ANALISIS PENGARUH PROMOSI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEJABAT STRUKTURAL ESELON III DI PEMERINTAH KABUPATEN LOMBOK BARAT - Muhammad Busyairi (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This study aims to analyze: (1) the effect of promotion on job satisfaction among echelon IIIofficials in West Lombok regency, (2) the effect of promotion on their work motivation, (3) the effectof work motivation on their satisfaction, (4) the effect of promotion on their job satisfaction throughthe use of work motivation.This research is categorized as a associative causal study. The techniqueof data collection employed literature studies and questionnaires. Population of the study covered169 echelon III officials in West Lombok regency. The data were analyzed using Path Analysistechnique. Results of the study show that: (1) promotion had a positive effect on work motivation; (2)promotion had a positive and significant effect on the work motivation (3) work motivation had apositive and significant impact on the job satisfaction (4) promotion had a positive and significanteffect on the job satisfaction through the provision of motivation from the Government of WestLombok Regency. Results of the study recommend that the authorities of West Lombok regencyshould conduct the promotion process in a fair way by considering the educational background,competence and performance of its staff. Thus, their work motivation and job satisfaction wouldimprove significantly.Keywords: promotion, work motivation, and job satisfaction.